Density Fluctuations across the Superfluid-Supersolid Phase Transition in a Dipolar Quantum Gas - J. Hertkorn; J.-N. Schmidt; F. Böttcher; M. Guo; M. Schmidt; K. S. H. Ng; S. D. Graham; H. P. Büchler; T. Langen; M. Zwierlein; T. Pfau (Physical Review X, 2021)
Phase transitions share the universal feature of enhanced fluctuations near the transition point. Here, we show that density fluctuations reveal how a Bose-Einstein condensate of dipolar atoms spontaneously breaks its translation symmetry and enters the supersolid state of matter—a phase that combines superfluidity with crystalline order. We report on the first direct in situ measurement of density fluctuations across the superfluid-supersolid phase transition. This measurement allows us to introduce a general and straightforward way to extract the static structure factor, estimate the spectrum of elementary excitations, and image the dominant fluctuation patterns. We observe a strong response in the static structure factor and infer a distinct roton minimum in the dispersion relation. Furthermore, we show that the characteristic fluctuations correspond to elementary excitations such as the roton modes, which are theoretically predicted to be dominant at the quantum critical point, and that the supersolid state supports both superfluid as well as crystal phonons.